Mechanical and electrical properties of graphene nanosheet reinforced copper matrix composites materials produced by powder metallurgy method - Albartouli Ahmed Basheer Mohammed; Uzun Arif (National Library of Serbia, 2023)
This study investigated the mechanical and electrical properties of copper matrix composite materials reinforced with graphene nanosheets. The composite materials were produced using the powder metallurgy method, with several weight percentages graphene nanosheets (0, 0.5, 1 and 1.5) added to the copper matrix powders. The mixed powders were compacted unidirectionally in a steel mold at different pressures (500, 600 and 700 MPa) and sintered in an argon atmosphere at different temperatures (850, 900 and 950?C). Furthermore, the sintered samples were subjected to microstructure analysis, hardness and electrical conductivity measurements. The results showed that the microstructure exhibited porosity and agglomeration with increasing amounts of graphene nanosheets, resulting in a decrease in relative density up to 87.4%. The highest electrical conductivity was 76.59 IACS (0% GNS-500 MPa-950?C), while the lowest was 43.49 IACS (1.5% GNS-500 MPa-850?C). The addition of graphene nanosheets resulted in a relative increase in hardness of up to 1%.
Keywords: powder metallurgy; gns-cu composite; electrical conductivity; Chemical technology; TP1-1185